Public Financial Reporting Practices, Regulations and Accountability for State-Owned Enterprises in Kenya - Deori, Pujya Khattiya; Poda, Naphatsnan (Journal of Global Economy, Business and Finance, 2024)
This paper assesses the financial reporting and regulation practices in state owned corporations in Kenya. The paper reviews available literature on financial reporting and regulation practices in state owned corporations in Kenya. State owned corporations are instrumental in the delivery of health, education, transport, and other critical services as they continue to account for a significant portion of economic society. This study is motivated by the challenges facing state owned corporations in Kenya as per the reports of Auditor general on weaknesses of financial reporting practices in state owned corporations in Kenya (2021/2022).The report shows that there is poor accountability in most of state owned corporations for the use of resources provided by the government which result into fraud, waste, corruption, misappropriation of funds, and limits their ability to deliver adequate public services and maintain their good standing. The report further shows that, most of state-owned organizations are also faced with challenge of poor financial reporting practices as reflected in misuse of financial resources, resulting in constant loss making. The focus of this research will be to examine the relationship between public financial reporting practices and accountability of state-owned corporations in Kenya. The study shall be guided by the following objectives: To establish the relationship between budgeting practices, financial statements, staff competencies, IFMIS and regulation practices on accountability of state owned corporations in Kenya. The study shall adopt budget participatory theory, theory of inspired confidence and Agency theory. Exploratory research design shall be adopted. The target population of study is comprised of 187 state owned corporations in Kenya. A sample of 127 firms will be selected using a stratified random sampling technique. The respondents will be senior officers in finance/governance, compliance, IT and HR, who are considered in the study sample. Semi structured questionnaires will be designed to collect research data with drop and pic method shall be adopted. The collected data shall be analyzed using a mixture of quantitative and qualitative research approach. Results and findings shall be presented in tables and figures. The study recommends that the finance managers of state-owned corporations should closely work with budgeting committee to ensure effective budget compliance and full implementation for improved accountability of the corporations. The accountants of state-owned corporations should ensure that regular financial statements are prepared in line with International Financial Reporting Standards. Further, it is recommended that IFMIS connectivity should be improved, and that staff capacity building should be carried out. The policy makers of all state-owned corporations should regularly review and advise the management on regulations that are likely to affect accountability in their entities. The chief Executive Officer of State-owned corporations should initiate policy guidelines regarding corporate financial governance and ensure that there is full implementation with regular feedback. The paper also recommends the need to strengthen the sanction enforcement mechanism for those found involved in financial malpractices.